Comparative Transcriptome Analysis Between a Spontaneous Albino Mutant and Its Sibling Strain of Cordyceps militaris in Response to Light Stress - Wang, Fen; Liu, Qing; Zhang, Jiaojiao; Liu, Kuanbo; Li, Kuan; Liu, Guijun; Dong, Caihong (Frontiers in Microbiology, 2018)
Albinism has been used for new variety screening in some edible mushrooms and the underlying mechanisms are fascinating. Albino fruiting body of Cordyceps militaris, a well-known edible fungus and model organism for Cordyceps, has the potential to be a nutraceutical or functional food due to its high content of metabolites and antioxidant activities. In this study, a spontaneous albino mutant strain (505) of C. militaris was obtained. In comparison to its normal sibling strain (498), the albino strain stably remained white in response to light and had significantly decreased conidia and carotenoid production but accumulated more cordycepin. Transcriptome analysis of both strains revealed that all the seven photoreceptors were expressed similarly in response to light. However, many more genes in the albino strain were differentially expressed in response to light than its sibling strain. The significantly enriched pathways in 498L vs. 505L were mainly associated with replication and repair. Some secondary metabolite backbone genes including those encoding DMAT, two NRPS-like proteins, three NPRS, and lanosterol synthase were differentially expressed in the albino when compared with that of the normal strains. Transcriptome and real-time quantitative PCR analyses indicated that some cytochrome P450s and methyltransferases might be related to the phenotypic differences observed between the two strains. This study compared the genome-wide transcriptional responses to light irradiation in a spontaneous albino mutant and its normal sibling strain of an edible fungus, and these findings potentially pave the way for further investigation of the pigment biosynthetic pathway.